1990
DOI: 10.1111/j.1464-410x.1990.tb07190.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Renal Colic by Prostaglandin Synthetase Inhibitors and Avafortan (Analgesic Antispasmodic)

Abstract: In a study of the pain-relieving effect of 3 drugs commonly used to treat acute renal colic in this hospital, intravenous indomethacin and intramuscular diclofenac (prostaglandin synthetase inhibitors) were compared with intravenous Avafortan (analgesic antispasmodic). As first-line analgesics, prostaglandin synthetase inhibitors, if given intravenously, offer an effective alternative to Avafortan. Of 145 patients studied, 32 required a second injection for complete relief of pain. Administering a second dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…However, spontaneous and regular contractions of ureteral strips have also been reported. It may be hypothesized that anoxia may have provoked spontaneous ureteral activity in some cases, as it occurred more often in abnormal or damaged ureters [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, spontaneous and regular contractions of ureteral strips have also been reported. It may be hypothesized that anoxia may have provoked spontaneous ureteral activity in some cases, as it occurred more often in abnormal or damaged ureters [4].…”
Section: Discussionmentioning
confidence: 99%
“…The most effective mode of administration is the intravenous route, but in 55% of cases, side effects occur. However, since these drugs also decrease the renal blood flow, they may induce renal failure, especially in obstructed kidneys [4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of synthetic prostaglandin inhibitors, such as nonsteroidal anti-inflammatory drugs (NSAIDs), is considered nowadays the best and most effective way of treating patients who suffer from renal colics [4,6,7]. Nevertheless, NSAIDs exert undesirable side effects on the excretory tract: Perlmutter et al [8] demonstrated that the use of NSAIDs in subjects with acute obstruction of the excretory tract greatly reduces PRF, which remains low for a long period of time.…”
Section: Introductionmentioning
confidence: 99%
“…One family of drugs in the treatment of ure teral colics are prostaglandin synthase inhibitors [ 10], These drugs do not only relieve pain, but also facilitate stone passage [11], The most effective route of adminis tration is the intravenous, but in 55% of the cases side effects were reported. However, since these drugs also decrease renal blood flow, they may induce renal failure, especially in obstructed kidneys [ 12,13], The aim of our study was to analyze the PDE isoen zymes present in the human ureter and to evaluate the functional effects of isoenzyme-specific inhibitors in this tissue in vitro.…”
Section: Introductionmentioning
confidence: 99%